circ-SIRT1 Promotes Colorectal Cancer Proliferation and EMT by Recruiting and Binding to eIF4A3 - Xiangjie Wang; Shuang Liu; Bin Xu; Yabin Liu; Peng Kong; Changlin Li; Binghui Li (Analytical Cellular Pathology)
Circular RNA (circRNA), a recently identified type of endogenous noncoding RNA, has been implicated in the occurrence and development of a variety of tumors; however, whether circ-SIRT1, derived from pre-mRNA of the parental SIRT1 gene, is involved in colorectal cancer (CRC) remains unknown, as do the potential underlying mechanisms. The expression of circ-SIRT1 in CRC cells and tissue was detected by RT-qPCR. Colony formation and Cell Counting Kit-8 assays were used to evaluate the effect of circ-SIRT1 knockdown on the proliferative ability of CRC cells. Wound healing and Transwell assays were used to assess the effect of circ-SIRT1 knockdown on the migratory and invasive capacity of CRC cells. RNA immunoprecipitation and RNA pull-down assays were employed to validate the binding of circ-SIRT1 to EIF4A3. Western blot was used to identify the changes in the expression of EIF4A3 and EMT-related proteins. The RT-qPCR results showed that circ-SIRT1 was highly expressed in CRC cells and tissue and was positively correlated with the depth of tumor invasion. Knocking down circ-SIRT1 inhibited the proliferation and invasion of CRC cells and EMT. We further found that EIF4A3 could bind to circ-SIRT1, and that overexpressing circ-SIRT1 decreased the abundance of EIF4A3 at the mRNAs of the EMT marker proteins N-cadherin and vimentin. Combined, our findings suggested that circ-SIRT1 regulates the expression of EMT-related proteins by preventing EIF4A3 recruitment to the respective mRNAs. Our results further indicate that circ-SIRT1 functions as an oncogene in CRC by promoting the proliferation, invasion, and EMT of CRC cells through the circ-SIRT1/EIF4A3/N-cadherin/vimentin pathway.